2021
DOI: 10.2478/prilozi-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis-Related Peritonitis: Rate, Clinical Outcomes and Patient Survival

Abstract: Peritoneal dialysis-related peritonitis remains the major complication and primary challenge to the long-term success of peritoneal dialysis (PD). The study aimed to analyze the peritonitis rate, the cause, the outcomes, and the association of peritonitis with the survival of patients on peritoneal dialysis. Patient data were collected retrospectively from medical charts. A total of 96 patients received peritoneal dialysis in the PD center from 1 January 1999 to 31 December 2018. Episodes of peritonitis (n=159… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…analysis in a recent study (72). Another study revealed the causative microorganisms in PDE samples based on traditional culture and found both gram-positive bacteria (i.e., Staphylococcus, Streptococcus, Enterococcus) and gram-negative bacteria (i.e., Escherichia, Klebsiella, Pseudomonas) which are partially consistent to our study (74).…”
Section: The Relative Abundance Of Fungal Classificationsupporting
confidence: 91%
“…analysis in a recent study (72). Another study revealed the causative microorganisms in PDE samples based on traditional culture and found both gram-positive bacteria (i.e., Staphylococcus, Streptococcus, Enterococcus) and gram-negative bacteria (i.e., Escherichia, Klebsiella, Pseudomonas) which are partially consistent to our study (74).…”
Section: The Relative Abundance Of Fungal Classificationsupporting
confidence: 91%
“…Peritoneal dialysis (PD) is an effective renal replacement therapy (1), however, the proportion of ESRD patients treated with PD is lower than hemodialysis in developed countries (2). Clinical studies have demonstrated that peritoneal ultrafiltration declines gradually 2 -4 years after the initiation of PD (3)(4)(5). The induction of peritoneal fibrosis is a complex pathological event, and is characterized by epithelial-to-mesenchymal transition (EMT), activation of fibroblasts, deposition of extracellular matrix (ECM) components and angiogenesis (6).…”
Section: Introductionmentioning
confidence: 99%
“…Local inflammation of the periodontal tissue affects body systems by altering the levels of blood inflammatory mediators, increasing the probability of systemic inflammation in PD patients [ 7 , 13 ]. Peritoneal dialysis-associated peritonitis (PDAP) is the most common clinical complication of PD and seriously affects peritoneal ultrafiltration and dialysis efficiency, and it is an important cause of the termination of PD and even death [ 14 17 ]. Cardio- and cerebrovascular events (CCEs) are the first and most important cause of death among PD patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%